2013
DOI: 10.1111/jhn.12155
|View full text |Cite
|
Sign up to set email alerts
|

A mobile health intervention for weight management among young adults: a pilot randomised controlled trial

Abstract: The piloted mHealth programme provided some short-term positive changes in weight, nutrition and physical activity using a low cost, convenient delivery method for this population. However, changes were no different from those observed among controls. This might partly be explained by intervention participants' low engagement with the programme, which is likely to require further modification to provide more regular, personalised, monitored support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
287
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(297 citation statements)
references
References 38 publications
5
287
2
3
Order By: Relevance
“…Of 6 studies that compared combined interventions with conventional interventions, 4 reported significantly higher effect on adiposity in the combined intervention group. Of 5 RCTs evaluating combined interventions and diet, 3 found significant improvement in dietary intake 17, 18, 19, 20. Of 2 studies assessing combined interventions and conventional interventions, 1 reported significantly higher effect on diet in the combined intervention group and 1 reported no effect in either intervention group.…”
Section: Resultsmentioning
confidence: 99%
“…Of 6 studies that compared combined interventions with conventional interventions, 4 reported significantly higher effect on adiposity in the combined intervention group. Of 5 RCTs evaluating combined interventions and diet, 3 found significant improvement in dietary intake 17, 18, 19, 20. Of 2 studies assessing combined interventions and conventional interventions, 1 reported significantly higher effect on diet in the combined intervention group and 1 reported no effect in either intervention group.…”
Section: Resultsmentioning
confidence: 99%
“…Also described in Table 3, the majority of the studies were randomized trials (n=12) 6,8,9,17,18,[21][22][23][27][28][29]31 ; followed by randomized controlled pilot studies (n=3) 7,10,25 ; convenience sample pilot studies (n=2) 1,24 ; quasi experimental (n=1) 30 ; mixed method observation cohort study (n=1) 11 ; and prospective cohort study (n=1) 32 .…”
Section: Methodsmentioning
confidence: 99%
“…Outside of the US, study locations included Australia (n=3) 7,21,25 , New Zealand (n=2) 1,18 , Netherlands, Canada, United Kingdom, and India 8,17,24,27 . Sample size and gender also varied greatly.…”
Section: Settings and Samplementioning
confidence: 99%
See 2 more Smart Citations